Pediatric Portal Hypertension: Etiology and Management - Shah, Jay H.; Krndzija, Harun; Hawkins, C. Matthew (Digestive Disease Interventions, 2022)
Portal hypertension is a known cause of morbidity and mortality in children. With a paucity of data and no standardized algorithm for treatment, a comprehensive understanding of this disease process is necessary for pediatric interventional radiologists, hepatologists, and surgeons who collaborate to care for these patients. While associations can be drawn to adult disease, the specifics of pediatric portal hypertension necessitate a separate, multidisciplinary approach. This review provides a summary and update on the evaluation, management, and treatment of pediatric portal hypertension.
Keywords: pediatric portal hypertensions; liver disease; variceal bleeding